Três perspectivas sobre a pobreza no Brasil: armadilha da pobreza nutricional, infraestrutura e pobreza, subnutrição e mortalidade infantil - Campêlo, Guaracyane Lima (2013)
The thesis is composed of three articles with methodologies and different databases and aiming to analyze poverty from different perspectives. The first article entitled "Poverty nutrition trap: empirical evidence for the rural area of Brazil" investigates the impact of poor nutrition on labor productivity, analyzing poverty trap in relation to nutrition (APN). There is the effect of the intake of micronutrients (iron and vitamins A, B1 and B2) and calories on the incomes of the heads of households to the agricultural, non-agricultural self-employment and other jobs. Uses a variation of the method of Durbin and McFadden (1984) to correct for selection bias based on multinomial logit models. The data are from the Household Budget Surveys (IBGE) 2002-2003 and 2008-2009 for the rural area of Brazil. The results demonstrate that although micronutrient deficiencies still persist as public health problems in Brazil, there is an improvement in this period. The second article entitled "The impact of infrastructure on poverty in Brazil" is proposed to analyze the effect of investments infrastructure in strategic sectors of the economy (transport, energy, communication, health and sanitation) in reducing poverty controlling for other determinants such as economic growth, inequality, education, unemployment and government budget revenue for brazilian states, in the period 1995-2009. A model for dynamic panel data, estimated by generalized method of moments-system (MMG-S) in two steps, developed by Arellano-Bond (1991) and Blundel-Bond (1998) indicate, among other conclusions, a significant relationship between public investments in infrastructure and poverty, which are an effective tool in combating this. The other investigated variables play an important role in the dynamics of poverty in Brazil. The Granger causality test for panel data proposed by Hurlin and Venet (2001, 2004) and Hurlin (2004, 2005) validates the results. The third article entitled "Poverty, malnutrition and infant mortality in Brazil: regional evidence and its implications for public actions" verifies the impacts of anthropometric indices on child mortality (children aged less than five years) for Brazil. The indices applied for the children were based upon three measures: proportion weight by age; proportion of weight by height and the proportion of height by age. The empirical application relied on the estimations of three panel data econometric models, in which the cross sections units are the brazilian states and the time series in the period 2001- 2008. Controlling for other determinants, it could be concluded through the reliable estimates that theses anthropometric indices affect positively the infant mortality rate.